Learning Innovation Opportunities Using Interactive Multimedia to Facilitate Sociological Learning in Improving Collaboration Skills - Mutiara Kusuma Ananda Pramusita; Sariyatun Sariyatun; Hassan Suryono (PAEDAGOGIA, 2024)
The development and progress of technology has brought changes in the world of education. Digital learning media makes students more active in utilizing sophisticated technology to support activity learning. Convenience access to telephone mobile or telephone smart gives students more freedom to access the materials they need. Learning sociology teaches students the importance of someone as a creature working the same in life socially. Therefore, students need skills collaboration to support their development skills personal. Skills collaboration can supported with interactive multimedia as a means of learning. Interactive multimedia presents various features interactive in text, images, and videos. However, schools do not yet own facility adequate learning for to support enhancement skills and collaboration with students in matter technology. Types of research this study is the survey method. The focus study is 202 students in class X of a high school. Data collection methods include questionnaires and interviews. The analysis is through four stages, data collection, data reduction, withdrawal conclusion of initial data, and presentation results study. Research results show the need for interactive multimedia in learning sociology to increase skills in collaboration. Specifically, 50.2% of students have not yet done do activity collaborative in learning sociology using interactive multimedia. In addition, 95.5% of students require interactive multimedia to learn material sociology. Lastly, 95.5% of students use technology for study. Implications from this study are that students and teachers can optimize the utilization of technology with the development of interactive multimedia that can be used to reach objective expected learning that is increasing skills collaboration among students and make more students excel and do well in school the environment public. Based on the acquisition of analytical data, then concluded that the existence of interactive multimedia is required to increase skills collaboration students in learning sociology.